Organizational Citizenship Behavior in Online Transportation Drivers: A Mediation Model - Siswanto Siswanto; Masyhuri Masyhuri (Faculty of Economic and Business, 2022)
The research originality is the use of organizational commitment variable as mediation and object of research in transportation start-up companies that have not been studied before. The objective of this research was to examine the mediating role of organizational commitment between job involvement and organizational citizenship behavior (OCB). This research is used to develop knowledge about human resource management in start-up companies with partner status. The partial least square structural equation modeling technique is used to test quantitative data and hypotheses. The result of this research is that organizational commitment does not mediate the effect of job involvement on organizational citizenship behavior. Furthermore, job involvement has a significant positive effect on OCB. This study also provides the practical implication that employees who have a high commitment do not make them work extra because the status as partners is very different, so further discussion is needed. How to Cite:Siswanto., & Masyhuri. (2022). Organizational Citizenship Behavior in Online Transportation Drivers: A Mediation Model. Etikonomi, 21(1), 113-126. https://doi.org/10.15408/etk.v21i1.22665.